Biomimetic Actuators: Toward a New Generation of Smart Biomimetic Actuators for Architecture (Adv. Mater. 19/2018). Issue 19 (7th May 2018) - Poppinga, Simon; Zollfrank, Cordt; Prucker, Oswald; Rühe, Jürgen; Menges, Achim; Cheng, Tiffany; Speck, Thomas
Abstract : Motile hygroscopic plant structures simultaneously fulfill functions as a sensor, actuator, and support structure in a single materials system, making them ideal candidates for the development of biomimetic hydraulic actuators. In article1703653, Simon Poppinga and co‐workers discuss related biomimetic approaches, provide a theoretical concept to escape the poroelastic timescale limitation, show possibilities to improve the mechanical properties of the actuator, and treat the implementation of tropistic movement behavior.